2016
DOI: 10.1002/mabi.201600080
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Mesenchymal Stem Cells Toward Quality Cartilage Using Fibrinogen‐Based Nanofibers

Abstract: Mimicking the complex intricacies of the extra cellular matrix including 3D configurations and aligned fibrous structures were traditionally perused for producing cartilage tissue from stem cells. This study shows that human adipose derived mesenchymal stem cells (hADMSCs) establishes significant chondrogenic differentiation and may generate quality cartilage when cultured on 2D and randomly oriented fibrinogen/poly‐lactic acid nanofibers compared to 3D sandwich‐like environments. The adhering cells show well‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[3,120] Good biocompatibility of electrospun fibrinogen fibers was found with neonatal rat cardiac fibroblasts, [121] human bladder smooth muscle cells, [122] endothelial cells, [123] and human adipose derived mesenchymal stem cells. [124] However, a major disadvantage of electrospinning is the high protein concentration of more than 100 mg mL −1 required to produce nanofibrous fibrinogen scaffolds with reproducible diameters and porosity. [3,117,125] Acidic pH Conditions, Heating, and Protein Binding: Wei and co-workers also observed fiber assembly of fibrinogen on hydrophilic mica under acidic pH conditions.…”
Section: Denaturing Buffer Conditionsmentioning
confidence: 99%
“…[3,120] Good biocompatibility of electrospun fibrinogen fibers was found with neonatal rat cardiac fibroblasts, [121] human bladder smooth muscle cells, [122] endothelial cells, [123] and human adipose derived mesenchymal stem cells. [124] However, a major disadvantage of electrospinning is the high protein concentration of more than 100 mg mL −1 required to produce nanofibrous fibrinogen scaffolds with reproducible diameters and porosity. [3,117,125] Acidic pH Conditions, Heating, and Protein Binding: Wei and co-workers also observed fiber assembly of fibrinogen on hydrophilic mica under acidic pH conditions.…”
Section: Denaturing Buffer Conditionsmentioning
confidence: 99%
“…In this respect, our sandwich-like construct provides ADMSCs with opportunity to receive stimuli from the third dimension, which enables comparison of their behavior in 2-D and 3-D environments. 18 It has to be mentioned that we already explored this construct for studies on the chondrogenic differentiation of ADMSCs 38 and surprisingly found that cells produces favorably cartilage in 2-D random samples versus their aligned counterparts, and also more than in 3-D conditions. 38 The same approach, but now applied for the osteogenic response, revealed a generally better ADMSCs differentiation in 3-D environment, while the effect of alignment was found only in respect to OSP gene expression.…”
Section: Qpcr Experimentsmentioning
confidence: 99%
“…18 It has to be mentioned that we already explored this construct for studies on the chondrogenic differentiation of ADMSCs 38 and surprisingly found that cells produces favorably cartilage in 2-D random samples versus their aligned counterparts, and also more than in 3-D conditions. 38 The same approach, but now applied for the osteogenic response, revealed a generally better ADMSCs differentiation in 3-D environment, while the effect of alignment was found only in respect to OSP gene expression. Similar studies with aim to emulate in vivo tissue structures used layer-by-layer approach to stack cell-seeded nanofiber meshes (aligned or random) into 3-D multilayered constructs.…”
Section: Qpcr Experimentsmentioning
confidence: 99%
“…The ideal scaffold should have a uniform structure, excellent biocompatibility and biodegradability, as well as suitable mechanical strength, thus providing a specific environment for cell and tissue function in vitro and in vivo (Yang, Du, & Chua, ). So far, various types of materials such as biopolymer‐based hydrogels (Sá‐Lima, Caridade, Mano, & Reis, ) or nanofibers (Forget et al, ), synthetic polymer‐derived scaffolds (Izal et al, ) or hydrogels (Grant et al, ), and inorganic particle‐based nanocomposite hydrogels (Asadi et al, ) have been employed for cartilage regeneration. Particularly, synthetic, biodegradable polymers have been considered as useful scaffold materials, since their properties can be readily adjusted through the control of the polymerization reaction (Liu, Holzwarth, & Ma, ), but their biological efficiency as well as safety remain unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal scaffold should have a uniform structure, excellent biocompatibility and biodegradability, as well as suitable mechanical strength, thus providing a specific environment for cell and tissue function in vitro and in vivo (Yang, Du, & Chua, 2001). So far, various types of materials such as biopolymer-based hydrogels (Sá-Lima, Caridade, Mano, & Reis, 2010) or nanofibers (Forget et al, 2016), synthetic polymer-derived scaffolds (Izal et al, 2013) or hydrogels (Grant et al, 2008), and inorganic particle-based nanocomposite hydrogels (Asadi et al, 2018) have been employed for cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%